Membangun Situation Awareness Petugas AVSEC Terhadap Barang Bawaan Penumpang di Bandar Udara Komodo Labuan Bajo - Win Winda Wulandari; Siska Ayu Andarini (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Situation Awareness (SA) refers to an individual’s perception or response to understanding the conditions or state of their surrounding environment. For Aviation Security (Avsec) personnel, Situation Awareness is crucial as it impacts their performance and the success of their duties and responsibilities on the field. This study aims to explore how Avsec personnel develop Situation Awareness (SA) and the obstacles they face during the screening of passengers' baggage at Komodo Labuan Bajo Airport. The research employs a qualitative approach with a descriptive qualitative research design. Data collection for this study was conducted at Komodo Labuan Bajo Airport, involving interviews, observations, and documentation. The findings indicate that the Aviation Security (Avsec) personnel at Komodo Labuan Bajo Airport have effectively implemented Situation Awareness (SA) and have reached Level 3 SA. This reflects their capability to understand and manage situations very well. The personnel not only adhere strictly to instructions but also take the initiative to observe suspicious passenger behavior. A deep understanding of procedures and good coordination enable them to handle both normal and emergency situations efficiently, ensuring safety and effectiveness in the screening of passengers' baggage.